The concept of Europe as a cultural identity - Shehu, Fatmir; Zejno, Bukuri (IIUM Press, International Islamic University Malaysia, 2017)
The long discussion on the making of Europe’s identity, from a political, economic, cultural or religious aspect, has, on one hand, paved the way for the unity of European nations, and created many misconceptions in the mind-set of both, the élite and the masses, the developed and undeveloped nations, on the other. The worry about the absorption of core principles of one’s culture within European Community and the superiority of high or élite culture towards popular culture or low culture has created numerous obstacles for the construction of Europe’s cultural identity. The thrust of this paper is to study the concept of Europe as a cultural identity, which is very essential for Europe’s unity as well it motivates its members to have a sense of self and co-existence peacefully. Besides, it contributes to their overall wellbeing and brings them closer regardless of their differences. The formation of Europe’s cultural identity has been examined by looking firstly at the development of major concepts, like “Europe,” “European culture,” “European language,” “cultural identity,” and secondly the essential elements of Hellenic, Roman, Christian, and Scientific traditions. The descriptive and analytical methodologies have been employed in this paper. The findings have given insights to the reality of the unity of European nations under the banner of culture and not religion.